INTERACTION BETWEEN DIETARY MINERAL AND PHYTASE ON BIOLOGICAL PERFORMANCES OF JAPANESE FLOUNDER, Paralichthys olivaceus. PART II. MINERAL DIGESTIBILITY AND VERTEBRAL MINERAL CONTENT - Asda Laining; Lideman Lideman; Shunsuke Koshio (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2015)
Interactive effects between dietary inorganic phosphorus (IP) and phytase (P) on mineral digestibility and vertebral mineral content were investigated in a 30 days feeding trial followed by three weeks digestibility trial with Japanese flounder, Paralichthys olivaceus. Eight experimental diets were formulated based on two levels of dietary Ca at 0% and 0.2% combined with either 0% or 0.25% of dietary IP and either with 0 and 2,000 fytase unit (FTU)/kg of phytase in diet, respectively. Result indicated that digestibility of total phosphorus significantly increased by three dietary compounds where the highest was observed in fish fed diet contained 0.25% IP and 2,000 FTU phytase/kg and dietary Ca also included in diet. Significant interaction was only detected between dietary IP and P on this parameter. Supplementation of IP and Ca not phytase significantly improved Ca digestibility. Ca digestibility was very poor when dietary IP and Ca were not supplemented in diet even with when phytase supplemented in diet. There was significant interaction between dietary IP and Ca on Ca digestibility. Vertebral total phosphorus, Ca, and Mg content as well as Ca:P ratio were significantly enhanced by dietary IP and phytase. Dietary Ca has significant effect only on vertebral total phosphorus. Interaction between dietary IP and Ca was significantly found on vertebral Ca content and Ca:P ratio. No significant second-order interaction was observed among the three dietary mineral on overall parameters. Based on total phosphorus and Ca digestibility as well vertebral phosphorus content found in this study, dietary IP, Ca, and phytase at rate of 0.25%, 0.2%, and 2,000 FTU phytase/kg diet, respectively are needed to supplement in diet for a better mineral absorption and bone mineralization.